SIMULATION MODEL OF A VERTICALLY INTEGRATED SUPPLY CHAIN: A CASE STUDY - Byrne, P J; Heavey, Cathal (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This paper reports on the successful development and use of simulation for the analysis of a vertically integrated supply chain. Simulation has only recently been applied to the analysis of industrial supply chains and this model differs from existing work in this area in that the manufacturing function is modelled in detail. This is contrast to the logistical models developed using simple lead times to represent manufacturing. This paper reports on the scale of system being analysed, the type of data required to populate such a model, such as product routings, standard times, work centre capacities and shift cycles and the level of detail included in the stl!dy and the performance outputs from the model. Using this model experiments were carried out to analyse the effect of stocking policies, production controls, changing demand trends and the effect of forecasting and information sharing on supply chain performance measures. One such experiment to determine the effective trade-off from operating three different finish stocking policies is outlined in detail. These experiments provide management with a useful tool for decision support in relation to both strategic and production strategies.